Analysis Of Nursing Service Quality Strategy Indicators On The Perception Of Satisfaction Of Inpatients At Royal Prima Medan Hospital - Tri Suci; Maya Sari Mutia; Cindy Stefanie Sinaga (CV. Inara, 2025)
In conditions of tight competition, the main thing that hospitals need to prioritize is a strategy to improve the quality of service to their patients. The quality of nursing services indicates the quality of health services. Nurses determine the image of health service institutions in society. This research aims to analyze indicators of nursing service quality strategies on the perception of satisfaction of inpatients at RSU Royal Prima Medan. This type of research is quantitative descriptive. The population in this study was inpatients at RSU Royal Prima from January 2024 to February 2024, totaling 300 patients. The sampling technique in this research used an accidental sampling technique with a sample size of 300 patients. Data analysis used SEM and SPSS, including univariate, bivariate, and multivariate analysis. The research results showed that the majority of respondents in this study were 31-40 years old, 137 (45.7%); the majority were female, 215 (71.7%); and had a PT (higher education) education, 157 (52.3%). There is an influence of the reliability service quality strategy indicator on the perception of satisfaction of inpatients at RSU Royal Prima Medan, there is an influence of the responsiveness service quality strategy indicator on the perception of satisfaction of inpatients at RSU Royal Prima Medan, there is an influence of the assurance service quality strategy indicator on the perception of satisfaction of inpatients inpatients at RSU Royal Prima Medan, there is an influence of the empathy service quality strategy indicator on the perception of satisfaction of inpatients at RSU Royal Prima Medan, there is an influence of the tangible service quality strategy indicator on the perception of satisfaction of inpatients at RSU Royal Prima Medan, Service quality strategy indicator variable The most influential influence on the perception of satisfaction of inpatients at RSU Royal Prima Medan is the reliability service quality strategy indicator variable.